Import and release of nutrients during the first five years of plant litter decomposition. (January 2023) - Spohn, Marie; Berg, Björn
Abstract: During the initial stages of leaf and needle litter decomposition, microorganisms face nitrogen (N) and phosphorus (P) scarcity since plant litter is very N- and P-poor compared to microbial biomass. The processes that microorganisms use to cope with the unfavorable stoichiometry, such as transport of nutrients into decomposing litter, are still not fully understood. The aim of the study was to explore the import and release of nutrients (N, P, K, Mn, Ca, and Mg) into and from decomposing Norway spruce ( Picea abies Karst) and Scots pine ( Pinus silvestris L.) needle litter. For this purpose, we conducted a paired-stand litterbag study at eight temperate and boreal forest sites in Sweden that each have a spruce and a pine stand, over a period of five years. The mass of N in decomposing spruce and pine needle litter increased during the first 172 and 356 days, on average by 19% and 30%, respectively, compared to the initial masses of the element in the litter. The mass of P in pine litter increased during the first 526 days of decomposition, on average by 48%. Net release of N from spruce litter, relative to the initial N amount, only began after 895 days of decomposition. Net release of N and P from pine litter, relative to the initial amounts of the elements, started only after 1097 days. In contrast, K, Mn, Ca, and Mg were released right from the beginning of the decomposition process. The results show that N and P import into decomposing plant litter is a quantitatively important process in temperate and boreal coniferous forests during the first stage of litter decomposition when N and P concentrations are low. Nutrient import alleviates stoichiometric imbalance between the microbial biomass and the litter and likely contributes to microbial nutrient acquisition. Highlights: Mass of N in spruce litter increased by 19% during the first 172 days of decomposition. Mass of N in pine litter increased by 30% during the first 356 days of decomposition. Mass of P in pine litter increased by 48% during the first 526 days of decomposition. Net release of N and P from litter only began after 895–1097 days. N and P import into decomposing needle litter is a quantitatively important process.